Mapping the decision-making factors of small-scale fishers: a case study of Penang - Gao, Tianlin (2024)
Small-scale fisheries are crucial for global food security and economic development but face numerous challenges. Understanding their decision-making processes is vital for developing effective management strategies. The study employs a qualitative case study approach, including expert consultations and semi-structured interviews with 25 fishers. Factors were identified using qualitative thematic analysis, then filtered by frequency and importance. Causation between decisions and factors were demonstrated by causal mapping. The results are presented in three decision-making maps, each outlining a specific type of decision-making process: daily operational decisions, strategic fishing and sales decisions, and community involvement and collective action decisions. The factors influencing these decisions show a complex interplay across economic, social, and environmental dimensions. Operational decisions are predominantly shaped by immediate environmental conditions, while strategic decisions depend on long-term financial stability and market dynamics. Decisions involving community involvement are deeply rooted in social identities and interests, reflecting broader socio-political engagements. Findings reveal that fishers adopt stability-focused strategies to cope with the unpredictability of income and expenses, inadvertently ensnaring themselves in a cycle of precarious resilience. The study also highlights a strong desire among fishers for public participation, spurred by political marginalization. Additionally, the local context such as community network and institutions significantly influence their decisions. This study can be utilized to inform policy and program designs, ensuring interventions are tailored and locally relevant. Specific policy recommendations include enhancing financial literacy and access to credit, fostering an inclusive development process, and strengthening community-based organizations to support the fishery community. Future research should incorporate quantitative methods and broader stakeholder perspectives to understand the factors influencing small-scale fishers’ decisions more comprehensively.